Influence of barite particulate filler on the mechanical behaviour of carbon fiber reinforced LY556 epoxy matrix composites. (January 2022) - Benin, SR; Selvakumar, G; Sumathi, M; Bright, Renjin J
This work is intended to explore the influence of barite particulate filler on the mechanical behaviour of carbon fiber (Cf ) reinforced polymer matrix (CFRP) composites. The carbon fiber utilized for the study was T300 grade and the polymer matrix utilized was LY556 epoxy resin (Ep r). The CFRP composites prepared with 55 weight (wt.) % T300 carbon fiber and 45 wt.% LY556 epoxy resin without barite particulate filler was utilized for control experimentation. The CFRP composites with barite filler were prepared by varying the proportion of barite particles from 2.5 wt.% to 15 wt.% in steps of 2.5 wt.%. The composites were prepared using the hand lay-up process and the barite particles were mixed with the epoxy resin by means of ultrasonic agitation. The prepared composites were subjected to tension, compression, hardness, flexural and impact testing. The CFRP composites with 10 wt.% barite particles yielded the best tensile strength, hardness and impact strength. The tensile strength, hardness and impact strength attained an increase of 13.18%, 5.6% and 18.68% respectively, compared to the CFRP composite without barite filler. The compressive strength of the CFRP composite with 15 wt.% barite filler was observed to be more than twice the compressive strength of the CFRP composite without barite filler. However, the flexure strength reduced steadily with the addition of barite particulates. The fractured surface morphologies of the prepared composites were characterised using the Scanning Electron Microscope (SEM). The chemical composition and morphology of barite powder was analysed using Energy Dispersive X-Ray Spectroscopy (EDX) and SEM, respectively.